Trinidad and Tobago : 2008 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Trinidad and Tobago. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
The staff report for the 2008 Article IV Consultation of Trinidad and Tobago highlights economic developments and policies. Faced with a prospective decline in energy resources, the government has embarked on an ambitious development and diversification strategy. External vulnerability is low as a result of large international reserves and low debt ratios, and the banking sector has entered the period of global turmoil from a position of strength and with little reliance on external borrowing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet